Risk factors of fatigue: a systematic review among transportation drivers - Che Hasan, Nurul Atikah; Karuppiah, Karmegam; Hamzah, Nurul Ainun; Mohd Tamrin, Shamsul Bahri (Universiti Putra Malaysia, 2021)
Fatigue is an inevitable problem in the workplace due to many factors. Transportation workers are susceptible to falling asleep at the wheel, feeling tired and drowsiness, prolonged mental and physical exertion, sleep deprivation, which will later result in fatigue. The objective of this paper is to provide a comprehensive review of driver fatigue, documenting potential relationships between demographics and work factors with prevalence of risk factors among transportation drivers. Related literature search was done using PubMed, SCOPUS, and ScienceDirect to review some articles related to factors influencing fatigue among transportation workers which was published between years 2000 to 2021. The most significant risk factors were poor quality and quantity of sleep, prolonged driving in a day and work-related factors. Therefore, further research should be directed towards assessing and implementing a standardized measurement of work fatigue. This could help the industry in precisely managing and measuring fatigue and sleepiness.